Preschool Children's Prosocial Responsiveness to Their Siblings' Needs in Naturalistic Interactions: A Longitudinal Study. Issue 6 (18th August 2019) - Tavassoli, Nasim; Recchia, Holly; Ross, Hildy
ABSTRACT: Research Findings : Siblings' interactions in early childhood may provide a unique context for understanding others' needs and fostering prosociality. This 2-year longitudinal study examined children's prosocial responsiveness to their siblings' needs during naturalistic interactions. European-Canadian sibling dyads ( N = 39) were observed in their homes for a total of 18 hours – when they were age 2 and 4 years and 2 years later. Prosocial opportunities were identified from children's manifestations of need and coded for types of responses to such needs. Analyses indicated that younger siblings manifested more cues indicating a need. Siblings often expressed their needs explicitly through direct verbal or nonverbal requests. Alongside situational cues and parental intervention, direct verbal requests were particularly likely to elicit prosociality. Children engaged in helping more than sharing, followed by comforting and protecting. Opportunities to share were rejected more than other types of prosocial behaviors. With age, children were more likely to help, and less likely to refuse to share. With regards to birth order, 4-year-old firstborns engaged in helping, comforting, and protecting (but not sharing) more than 4-year-old secondborns. Practice or Policy : Findings have implications for parents by suggesting ways in which prosociality can be fostered within the sibling relationship in early childhood, and for researchers by extending recent theories of early prosociality from experimental settings to naturalistic interactions.